Comparative studies in method for stratigraphical structure measurement of ice cores: Identification of cloudy bands - Takata, Morimasa; Shoji, Hitoshi; Miyamoto, Atsushi; Shimohara, Kimiko (Polar Research Institute of China - PRIC, 2003)
Cloudy bands are typical stratigraphic structure in deep ice core. Detailed recording of cloudy bands is important for dating of ice core since pair of series cloudy band and clear layer is corresponds to annual layer and it sometimes corresponds to volcanic ash layer. We developed two type scanners, transmitted light method and laser tomograph method for the stratigraphic study. Measurements were carried out for NGRIP deep ice core, which containing many cloudy bands, using the two type scanners and digital camera. We discussed about the possibility of identification of cloudy bands by each method and about advantage and disadvantage of measurements and their results.